KAJIAN MUSIK KECAPI DELAPAN DEWA PADA ETNIS TIONGHOA SINGKAWANG KALIMANTAN BARAT - Utami, Risky; Mering, Aloysius; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to examine the Music of the Eight Immortals of the Singkawang Tionghoa of West Kalimantan. This study uses the discriminative method. The form of research conducted was qualitative. The approach used in this research was ethnomusicology approach with data collection techniques used are observation techniques, interview techniques and documentation techniques. Furthermore, in this study the researchers became the key instrument, which was then assisted with other tools such as recorder, interview guide and field notes. This study used source triangulation, which is collecting data from some informants is Tjin Nen Shin, Tai Siuk Jan, H. Norman, Tjit Tji Hui and Phang Khim Thin. The results of this research are: (1) Presentation form of Music of Dewa Kecapi that was played by eight people with eight musical instrument that is Jong Khim, Thew Hian, Nyi Fu, Jai Ko Yan, Cheng, Flute, Tok and Pui. At the time of the show, the players used the costumes of the Gods. Songs played on the Eight Dewa Music Performances were traditional Chinese songs and mandarin pop songs. The main function of Music of the Eight Immortals Music as entertainment. This research can be implemented to schools on cultural arts subjects or in extracurricular activities in schools. Keywords: Chinese, Music of the Eight Immortals of Gods, Study